Pengaruh Pengungkapan Corporate Social Responsibility terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Pemoderasi - Muhammad Hosen Bawafi; Adi Prasetyo (Jurnal Reviu Akuntansi dan Keuangan, 2017)
The purpose of this research is to examine the effect of Corporate Social Responsibility (CSR) disclosure on corporate value with profitability as a moderating variable. The research method that used in this research is quantitative and using analysis tool that is called SPSS. The result of this research is profitability variable as moderating variable proved empirically influence significantly correlation Corporate Social Responsibility and company value. In other words profitability can strengthen the influence of Corporate Social Responsibility to the value of the company at the time of high profitability of the company, and otherwise profitability can reduce the value of the company at the time of low profitability of the company. Keywords: CSR, Disclosure, Profitability, Value’s Company.